Mental Health Intervention for Violent Radicalization: The Quebec Model - Cécile Rousseau (Proceedings, 2021)
The place of clinical, medical, or health professional interventions in addressing violent radicalization is a topic of ongoing debate. Although violent radicalization is primarily a social phenomenon with significant psychological dimensions, the high prevalence of mental health “issues” and past psychiatric diagnosis in lone actors suggests that it may be useful to distinguish socialized actors who have strong ties to structured extremist organizations from relatively socially isolated actors who claim, and even boast about, virtual affiliation to extremist groups. For the latter, the potential efficacy of mental health interventions should be considered. However, because of the risk of profiling, stigmatization of minorities, pathologizing social dissent, and resistance, clinical intervention may cause harm and should be carefully evaluated. Until the effectiveness of clinical interventions in reducing radical violence is improved through evaluative research, exchanges about existing clinical models can be useful to support practitioners in the field and provide initial insights about good and potentially harmful practices. The Quebec model of clinical services to mitigate violent radicalization (secondary and tertiary prevention) is structured around three pillars: multiple access points to facilitate outreach and decrease stigma; specialized teams to assess and formulate treatment plans based on existing best evidence in forensic, social, and cultural psychiatry; and collaborative involvement with primary care services, such as community mental health, education, and youth protection institutions, which are in charge of social integration and long-term management. Beyond the initial assessment, the program offers psychotherapy and/or psychiatric interventions services, including mentorship to foster clients’ social integration and life-skill development. Artistic programs offering a semi-structured, nonjudgmental environment, thus fostering self-expression and creativity, are very well received by youth. A multimedia pilot program involving young artists has been shown to provide them with alternative means of expressing their dissent. Three years on from its inception, the preliminary evaluation of the Quebec clinical model by its partners and clinicians suggests that it could be considered a promising approach to address the specific challenges of individuals who present as potential lone actors at high risk of violent radicalization. The model does not, however, appear to reach many members of extremist groups who do not present individual vulnerabilities. While initial signs are positive, a rigorous evaluation is warranted to establish the short, medium, and long-term efficacy of the model, and to eventually identify the key elements which may be transferable to other clinical settings. In 2020, a five-year evaluative research project began to examine these questions. It is important to consider that any intervention can be harmful if due attention is not paid to structural discrimination and violence stemming from associated marginalization and exclusion. Clinical care can in no way replace social justice, equity, and human rights—all key pillars in primary prevention against violent radicalization. In the meantime, however, providing empathy and care in the face of despair and rage may prove most beneficial in decreasing the risk of violent acts.